Revision Surgical Treatment of a Second Lumbar Ewing Sarcoma. Issue 30 (July 2015) - Feng, Helin; Wang, Jin; Guo, Peng; Xu, Jianfa; Feng, Jiangang; Tuomo, Rantanen.
<x xml:space="preserve">Abstract</x> Abstract We report a case of a 58-year-old man who presented initially with lumbar pain. According to radiography, computed tomography, magnetic resonance imaging, and bone biopsy results, Ewing sarcoma (ES) was diagnosed. Tumor resection was performed, followed by chemotherapy and radiotherapy; pathology confirmed the diagnosis of ES. After surgery, the tumor recurred twice with progressive symptoms, meriting repeated excisional surgery. At the 4-year follow-up, the patient showed apparent improvement, with return of function and strength and resolution of pain. We discuss its clinical features and treatment in the light of the current knowledge.